کاریگەریی سۆشیال میدیا لەسەر حوکمڕانی دروست لە هەرێمی کوردستاندا (فەیسبووک بە نموونە) (توێژێنەوەی هەڵێنجراو) - ئەحمەد, پاڤێ جەمیل; حاجی, دلێر عەبدولخالق (Sulaimani Journal for Humanities, 2023)
The main objective of this research is to examine the extent of the impact of social media platforms and the social network of Facebook on political actors of formal and informal institutions of governance in the direction of following a kind of good governance in Kurdistan Region-Iraq. The research falls within a descriptive research approach. The research sheds light on the actors of formal governing institutions (members of parliament, ministers and members of the Judicial Council), as well as members of the media, the activists of civil society organizations. The research also employs survey methods and the questionnaire form among (240) participants. Next, a descriptive method through Statistical Package for the Social Sciences (SPSS) is used to analyse the data of the research. Among the most prominent findings of the research are; the majority of the sample of the research use Facebook and they follow up on political issues. A high percentage of participants are interested in the news and information related to good governance. In addition, a high percentage of the research samples publish their views and opinions on good governance through Facebook.